Challenges and Learning from Integrating Positive Psychology and Physical Exercise in the General Studies Department: Stories from Academic Praxis - Barrantes Brais, Kristy (2018)
This article is written as an account of experience resulting from an academic process conducted at the National University of Costa Rica, specifically at the Center for General Studies. The process aimed to promote the psychological well-being of university students through interventions in positive psychology (IPP) and physical exercise and, in turn, to develop skills in the academic staff of the Center for General Studies to manage positive psychology interventions. The methodology used in this academic project consisted of a series of interventions through the following three courses: 1) environment and health, 2) the image of the elderly person in the different texts and 3) literary expression workshop: story and poetry. The particular experiences of the interventions conducted in each course are outlined throughout this account. Likewise, challenges and learning for each course were obtained from these interventions. Training was provided on theoretical bases and the implementation procedure of the three IPPs reviewed. At the end of the training process, the relevant ways of including the principles and interventions of positive psychology and positive education in the methodological strategy of the course program were jointly determined. This experience generated possibilities for the different disciplines to work closely on a common plan for academic praxis in teaching and research; as a multidisciplinary pedagogy, it is rooted in interdisciplinarity.